2014
DOI: 10.1002/phy2.255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation in combination with motor practice on dexterous grasping and manipulation in healthy older adults

Abstract: Transcranial anodal stimulation (tDCS) over primary motor cortex (M1) improves dexterous manipulation in healthy older adults. However, the beneficial effects of anodal tDCS in combination with motor practice on natural and clinically relevant functional manual tasks, and the associated changes in the digit contact forces are not known. To this end, we studied the effects of 20 min of tDCS applied over M1 for the dominant hand combined with motor practice (MP) in a sham‐controlled crossover study. We monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 45 publications
8
32
1
Order By: Relevance
“…() provided preliminary evidence that a single application of a‐tDCS in older adults improved hand function in a task that mimics activities of daily living. Similar findings have been obtained for dexterous grasping (Parikh & Cole, ), motor sequence learning (Zimerman et al ., ), and visuomotor tracking (Goodwill et al ., ). Our findings are in line with such proof‐of‐concept studies in the elderly, as we demonstrated that MVF‐induced performance improvements could be further enhanced by concurrent a‐tDCS application.…”
Section: Discussionsupporting
confidence: 88%
“…() provided preliminary evidence that a single application of a‐tDCS in older adults improved hand function in a task that mimics activities of daily living. Similar findings have been obtained for dexterous grasping (Parikh & Cole, ), motor sequence learning (Zimerman et al ., ), and visuomotor tracking (Goodwill et al ., ). Our findings are in line with such proof‐of‐concept studies in the elderly, as we demonstrated that MVF‐induced performance improvements could be further enhanced by concurrent a‐tDCS application.…”
Section: Discussionsupporting
confidence: 88%
“…The incidence does not differ significantly between active and sham stimulation, indicating the effectiveness of the standard fade-in fade-out sham stimulation at least in naïve subjects (Hummel et al, 2010; Lindenberg et al, 2013; Manor et al, 2016; Parikh and Cole, 2014; Sandrini et al, 2014, 2016; Zimerman et al, 2013). Not surprisingly, the identification of the actually applied stimulation paradigm is more accurate after repeated sessions (Nilsson et al, 2015; Wallace et al, 2016).…”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 90%
“…About one-third of the studies published until 2016 in aging populations reported no occurrence of tDCS-related AEs without giving details (Table 7). The most commonly reported AEs were typical tingling and itching that usually occurred when stimulation began but were also reported under sham conditions, where stimulation was applied only for a short duration at the beginning of the session (Boggio et al, 2010; Fertonani et al, 2014; Gandiga et al, 2006; Harty et al, 2014; Hoff et al, 2015; Holland et al, 2011; Learmonth et al, 2015; Manenti et al, 2013; Parikh and Cole, 2014; Sandrini et al, 2014, 2016). …”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 99%
“…Several studies suggest that anodal tDCS can restore normal motor performance in healthy older subjects (Hummel et al, 2010; Parikh and Cole, 2014). In addition, this age-related decline in motor performance is also accompanied by an age-related decline in motor learning/motor adaptation (Seidler, 2007; Lustig et al, 2009).…”
Section: Application Of the Three Principles Of Polarizationmentioning
confidence: 99%